2017
DOI: 10.1038/srep46051
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress causes hypertension and activation of nuclear factor-κB after high-fructose and salt treatments

Abstract: There is evidence that diets rich in salt or simple sugars as fructose are associated with abnormalities in blood pressure regulation. However, the mechanisms underlying pathogenesis of salt- and fructose-induced kidney damage and/or consequent hypertension yet remain largely unexplored. Here, we tested the role of oxidative state as an essential factor along with high salt and fructose treatment in causing hypertension. Fischer male rats were supplemented with a high-fructose diet (20% in water) for 20 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
(36 reference statements)
3
28
0
Order By: Relevance
“…Interestingly, significant reduction in inflammatory and apoptotic markers has also been observed in HF‐treated cultured renal epithelial cells co‐incubated with imoxin (C16) ( Figure ). High fructose is often linked with oxidative stress , and in the present study, we have demonstrated that HF increases ROS generation in renal epithelial cells via activation of PKR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, significant reduction in inflammatory and apoptotic markers has also been observed in HF‐treated cultured renal epithelial cells co‐incubated with imoxin (C16) ( Figure ). High fructose is often linked with oxidative stress , and in the present study, we have demonstrated that HF increases ROS generation in renal epithelial cells via activation of PKR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with the role of PGI 2 in restraining oxidative stress in atherosclerotic vasculature (18) and in salt-induced hypertension (19,20) and the elevation of PGI 2 biosynthesis on the HSD (Figure 2), excretion of a major urinary F 2 -isoprostane (F 2 iP), an index of lipid peroxidation, was not significantly elevated in Ldlr KOs after 2 weeks on a HSD ( Figure 4C and 4D). However, rather than increase with Ipr deletion, F 2 iP excretion, just like BP, unexpectedly fell, consistent with the changes in mitochondrial dysfunction and oxidative phosphorylation genes observed in the renal medulla of Ipr/Ldlr DKO mice (mostly downregulated in the Ipr/Ldlr DKO) ( Figure 4D).…”
Section: A Hsd Activates Atrial Natriuretic Peptide Synthesis and Relsupporting
confidence: 75%
“…The immunohistochemistry of cardiac and renal tissue revealed higher NF-kB expressions in L-NAME-induced hypertensive rats relative to the control and rats co-treated with AI and captopril. The activation of NF-kB by oxidative stress has been associated with ventricular remodeling and arterial hypertension [60,61]. This was suggestive of the involvement of NF-kB signaling in cardiorenal dysfunction following L-NAME-induced hypertension.…”
Section: Groupmentioning
confidence: 90%